Behavior and thermal environment of Chinook salmon Oncorhynchus tshawytscha in the North Pacific Ocean, elucidated from pop-up satellite archival tags - Courtney, Michael B.; Evans, Mark D.; Strøm, John Fredrik; Rikardsen, Audun H.; Seitz, Andrew C. (Environmental Biology of Fishes, 2019)
This is a post-peer-review, pre-copyedit version of an article published in Environmental Biology of Fishes. The final authenticated version is available online at: https://doi.org/10.1007/s10641-019-00889-0 . Chinook salmon are widely distributed in offshore waters of the North Pacific Ocean, and of great economical and subsistence importance; however, little is known about their oceanic ecology. To address this, we tagged 43 Chinook salmon Oncorhynchus tshawytscha (57–100 cm) with pop-up satellite archival tags (PSATs) in the eastern (October– December) and central Bering Sea (August) to provide insights into the oceanic movements, behavior, and thermal environment of this species. The tags retrieved data for up to 260 days and end locations of tagged Chinook salmon spanned from the central Bering Sea ( n = 6), eastern Bering Sea/Aleutian Islands ( n = 20), and the Gulf of Alaska (n = 6). While at liberty, Chinook salmon occupied depths ranging from 0 to 538 m and experienced a thermal environment ranging from −0.6 to 13.5 °C. Overall, mean depths of individual fish ranged from 4.5 to 127.9 m, while median depths ranged from 1.3 to 99.5 m. Although sample sizes were not even among months of the year, Chinook salmon occupied the shallowest and warmest water in May–September and the deepest and coolest water in December–March. Diel depth-specific diving behaviors of Chinook salmon were found in some tag records, but these behaviors appeared to be variable among individuals and plastic in nature within individuals. Results from this study provide insights into movement, diving behavior and the thermal environment of individual Chinook salmon which may have future application in understanding its ecology and developing strategies to further reduce incidental catch of this species.